2014
DOI: 10.1039/c3lc51420j
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexing of miniaturized planar antibody arrays for serum protein profiling – a biomarker discovery in SLE nephritis

Abstract: In the quest to decipher disease-associated biomarkers, miniaturized and multiplexed antibody arrays may play a central role in generating protein expression profiles, or protein maps, of crude serum samples. In this conceptual study, we explored a novel, 4-times larger pen design, enabling us to, in a unique manner, simultaneously print 48 different reagents (antibodies) as individual 78.5 μm(2) (10 μm in diameter) sized spots at a density of 38,000 spots cm(-2) using dip-pen nanolithography technology. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…choice of solid support, spotting conditions) for recombinant antibody array production in future efforts, it is very likely that this key parameter can be even further improved [5]. In comparison, we observed mean/ median CV-values of 12% (range 5-27%) and 4% (range 0-11%) for the 1st and second generation of miniaturized recombinant antibody arrays produced based on DPN technology (NLP3000) [33,34]. Noteworthy, the CV-value has been found to be <30% for conceptual antibody nanoarrays [14-23, 25, 30], while conventional antibody microarrays (established platforms) regularly display CVs of <10% (recombinant antibody microarrays) [49] and <20% (polyclonal and monoclonal antibody microarrays [50,51].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…choice of solid support, spotting conditions) for recombinant antibody array production in future efforts, it is very likely that this key parameter can be even further improved [5]. In comparison, we observed mean/ median CV-values of 12% (range 5-27%) and 4% (range 0-11%) for the 1st and second generation of miniaturized recombinant antibody arrays produced based on DPN technology (NLP3000) [33,34]. Noteworthy, the CV-value has been found to be <30% for conceptual antibody nanoarrays [14-23, 25, 30], while conventional antibody microarrays (established platforms) regularly display CVs of <10% (recombinant antibody microarrays) [49] and <20% (polyclonal and monoclonal antibody microarrays [50,51].…”
Section: Discussionmentioning
confidence: 85%
“…Noteworthy, the CV-value has been found to be <30% for conceptual antibody nanoarrays [14-23, 25, 30], while conventional antibody microarrays (established platforms) regularly display CVs of <10% (recombinant antibody microarrays) [49] and <20% (polyclonal and monoclonal antibody microarrays [50,51]. The array-to-array and slide-to-slide reproducibility were found to be higher, which could be expected in evaluating non-normalized data [5,33,34]. Being a pilot study, we identified the efforts to apply such normalization strategies [5,33,34] to be more suited to follow-up studies, where the aim would be to evolve the platform from a proof-of-concept set-up to an optimized (established) methodology aiming to run (clinical) applications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations